Metabolism and plasma protein binding of 16 straight- and branched-chain parabens in in vitro liver and skin models. (April 2021) - Lester, Cathy; Hewitt, Nicola J.; Müller-Vieira, Ursula; Mayer, Manuela; Ellison, Corie; Duplan, Hélène; Genies, Camille; Jacques-Jamin, Carine; Fabian, Eric; Sorrell, Ian; Lange, Daniela; Schepky, Andreas; et al.
Abstract: Parabens are alkyl esters of 4-hydroxybenzoic acid (4-HBA), with short-chain parabens used as antimicrobials in cosmetics. We investigated the impact of chain structure on skin and liver metabolism. Incubations with primary human hepatocytes and human liver S9 indicated that methyl-, ethyl-, propyl- and butylparaben were rapidly metabolized to similar metabolites, including 4-HBA plus the corresponding alcohols. Liver and EpiSkin™ S9 were used to investigate the metabolism of 16 short and long straight- and branched-chain parabens. The rate of hydrolysis generally decreased with increasing chain length in liver S9, whereas the reverse was true for EpiSkin™ S9. Chain length also correlated with the number of metabolites, with more oxidized metabolites detected from longer chain parabens. The identity of the alcohol group impacted metabolism the most, in terms of the rate of metabolism and the contribution of cofactors. The majority of parabens (13/16) exhibited high plasma protein binding (PPB) (>90%); whereas, 4-HBA PPB was 38%. PPB was related to the LogP of the parabens. In conclusion, the major and common paraben metabolite in PHH, liver S9 and EpiSkin™ S9 was 4-HBA. The rate of metabolism, type of metabolite and contribution of hydrolysis was tissue-specific (liver, skin) and was influenced by the chain length (and hence LogP), structural isomeric form (straight vs branched), and/or the identity of the alkyl group. Short abstract: We investigated how the chain structure of parabens affects their metabolism by liver and EpiSkin™ S9. The major and common metabolite in primary human hepatocytes, liver S9 and EpiSkin™ S9 was 4-HBA plus the corresponding alcohols. The rate of metabolism, type of metabolite and contribution of hydrolysis was tissue-specific and influenced by the chain length, structural isomeric form (straight vs branched), and/or the identity of the alkyl group. Most parabens exhibited high PPB (>90%), whereas the PPB of 4-HBA was 38%. Highlights: Measured parabens metabolism by liver and EpiSkin and plasma protein binding (PPB). 4-HBA was the major metabolite in human hepatocytes, liver S9 and EpiSkin S9. Tissue-specific metabolic rate and metabolite identity. Chain length, isomeric form and alcohol group identity impacted metabolism. Most parabens exhibited high PPB (>90%), whereas the PPB of 4-HBA was 38%.